2022
DOI: 10.1007/s11282-022-00598-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiological features of oral and maxillofacial plasmablastic lymphomas

Abstract: Number of text pages: 11 Number of figures : 7Number of tables : 2 Number of references: 23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This feature however was still most commonly seen in BL. Another noteworthy finding was the presence of bone involvement in cases of plasmablastic lymphoma, as recently described by Nel et al 27 who showed a predilection for the posterior region of the maxilla 28 . Plasmablastic lymphoma bone involvement presented radiologically with poorly demarcated borders, loss of cortical integrity and cortical erosion or destruction, rather than cortical expansion.…”
Section: Discussionmentioning
confidence: 54%
“…This feature however was still most commonly seen in BL. Another noteworthy finding was the presence of bone involvement in cases of plasmablastic lymphoma, as recently described by Nel et al 27 who showed a predilection for the posterior region of the maxilla 28 . Plasmablastic lymphoma bone involvement presented radiologically with poorly demarcated borders, loss of cortical integrity and cortical erosion or destruction, rather than cortical expansion.…”
Section: Discussionmentioning
confidence: 54%